A Meta-Analysis of a Cohort Study on the Association between Sleep Duration and Type 2 Diabetes Mellitus - Huapeng Lu; Qinling Yang; Fang Tian; Yi Lyu; Hairong He; Xia Xin; Xuemei Zheng (Journal of Diabetes Research)
Objective. To study the association between sleep duration and the incidence of type 2 diabetes mellitus (T2DM) and to provide a theoretical basis for the prevention of T2DM through a meta-analysis. Methods. PubMed, Web of Science, Scopus, Embase, Cochrane Library, ProQuest, CNKI, Wanfang, VIP, and SINOMED were searched from their inception until May 2020. All cohort studies on the relationship between sleep duration and T2DM in adults were included. According to the inclusion and exclusion criteria, two authors independently assessed the literature and extracted the data. Metaregression and publication bias were evaluated, and sensitivity and meta-analyses were conducted with RevMan 5.3. Results. A total of 17 studies were collected, involving 737002 adults. The incidence of T2DM was 4.73% in short sleep duration (SSD) (t≤6 h), 4.39% in normal sleep duration (NSD) (6 h<t<9 h), and 4.99% in long sleep duration (LSD) (t≥9 h). The meta-analysis demonstrated that SSD increased the risk of T2DM compared with NSD (RR=1.22, 95% CI: 1.15-1.29, P<0.001), LSD increased the risk of T2DM compared with NSD (RR=1.26, 95% CI: 1.15-1.39, P<0.001), and the risk of T2DM has no significant difference between SSD and LSD (RR=0.97, 95% CI: 0.89-1.05, P=0.41). The sensitivity of each study was robust and the publication bias was weak. Conclusion. SSD or LSD can increase the risk of T2DM.